S telesno dejavnostjo in zdravim prehranjevanjem zoper depresijo. Je čas za udejanjanje integralnega pristopa k zdravljenju? - Pinter, Stanislav (Šport (Ljubljana), 2019)
In the 21st century, depression and depressive disorders became a personal and social problem, since they are - in their more pronounced form - diseases that globally present the main reason for disability and the fourth largest public health challenge. Today, scientists are unanimous that a single efficient treatment of depression is yet to be discovered. Besides psychotherapy, pharmacotherapy, with its antidepressants, presents the main approach to the treatment of depressive disorders. However, there exists a reasonable doubt about the efficacy of currently prescribed antidepressants and a strong concern over their side effects. Therefore, numerous authors have begun exploring alternative approaches, connected with lifestyle, which assist in regulating the symptoms of depression. Here, a lot of attention was also given to physical activity and healthy nutrition. Especially planned physical exercise and healthy nutrition were often a subject of discussion when talking about potential treatment of depression. The aim of this article is to assess the importance of the antidepressant effect of physical exercise and healthy nutrition through a relative review of scientific literature on the impact of physical activity and healthy nutrition on the symptoms of depression. This could provide a scientific basis for a potentially closer interdisciplinary cooperation of the experts from the field of sports, psychotherapy and medicine.
Keywords: antidepresivi; antidepressants; depresija (medicina); depression; healthy nutrition; physical activity; sport; sports activity; šport; športna dejavnost; telesna dejavnost; zdravo prehranjevanje